POTENTIAL OF AEK SIJORNI TOURISM OBJECT IN INCREASING TRADERS' INCOME IN AEK LIBUNG VILLAGE - lubis, nurhalimah (Prodi Perbankan Syariah UIN Sumatera Utara Medan, 2024)
AbstractAek Sijorni is a water tourism and recreation area that is visited by many because of its beauty, but even though Aek Libung Village has quite large natural potential, the income of traders in this village has still not reached its maximum potential. This could be caused by several factors, including lack of promotion and poor management of the Aek Sijorni tourist attraction. The aim of this research is to find out the potential of the Aek Sijornih tourist attraction in increasing the income of traders in Aek Libung Village. This research method uses a descriptive-qualitative approach. The data analysis technique is to carry out a strengths, weaknesses, opportunities and threats (SWOT) analysis. The data collection techniques used in this research are observation methods, interviews, and documentation of data validity by means of member checks. The research results show that the advantage lies in the uniqueness of Aek Sijorni, namely its clean and clear water. Apart from its uniqueness and beauty, it is rarely cloudy, even if it rains heavily. Weaknesses include access conditions and potholes; many officers and residents speak local languages; foreign tourists have difficulty understanding and communicating; and the skills of local communities need to be improved in using the national language. good and correct language so that visitors are happy if they receive good response and communication.Keyword : potential tourist attraction, Aek Sijornih, SWOT Analysis